Von Ashima zu Yi-Rap: die Darstellung nationaler Minderheiten in den chinesischen Medien am Beispiel der Yi-Nationalität - Senz, Anja-Désirée; Zhu, Yi (Duisburger Arbeitspapiere Ostasienwissenschaften, 2001)
From the old Chinese songs, we know that '56 Chinese brothers and sisters' live together in a big family. This expression refers to the number of nationalities living in P.R. China. However, many Han Chinese live far away from the National Minorities and they get to know their brothers and sisters mainly through media - books, newspapers or movies. As the function of media in China extended from politics to entertainment, it seems worthwhile to study the role which media serve in communicating knowledge (images) about National Minorities to the Han Chinese and what kind of images of the Minorities are actually transmitted. This paper tries to analyse the depiction of Yi Minority in Chinese media - in particular Chinese movies - from 1949 to the present. There are different phases of representations. Through a comparison of these phases, it can be analysed whether and in which way the depiction of National Minorities has been changed since 1949. The images of the Yi Minority transported through the media are of particular interest because they are a basis of communication and understanding but they also lead to misrepresentation and cliché.